Quantifying Risk in Waterfall Methodology: Case Study at Aplikasi Super - Bisono, Indriati Njoto; Arvin, Vincent; Soewandi, Hanijanto (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
In this paper, we presented a straightforward mathematical model based on Dynamic Programming to answer one of the biggest concern in Waterfall methodology, namely: quantifying risk. Our approach essentially resembles Elmaghraby (2005), but we have more stages and use uniform distributions. With this approach, we can show and quantify the risk in Waterfall methodology so that decision maker can understand the implication of his decision. Dynamic Programming solution also provides a blue print for adjusting decision if the early (previous) stage does not go as planned. A case study at Aplikasi Super with some sensitivity analysis is provided as a numerical illustration.